The Anthropic Principle in Cosmology and Theology - Mooney, Christopher F. (Horizons, 1994)
The "anthropic principle" has grown from scientific and philosophical reflection on the unlikely combination of circumstances needed, from the moment of the Big Bang through evolutionary history, to produce human life as we know it. This article describes the anthropic principle, in its "strong" and "weak" forms. It concludes with some thoughts on the possible theological implications of the anthropic discussion. From a theological perspective, the anthropic principle can be seen as part of the ongoing human effort to employ myth in the construction of a cosmology. It suggests both a sense of the design of the universe as well a the possible need for a Designer with some purpose and overall plan.